Characteristics of patients with falls and over time and by department - SAKATA, Noritaka; TAKAHASHI, Mariko; SATO, Mizuki; FUKUOKA, Yuka (Journal of Physical Therapy for Prevention, 2024)
Objective: The purpose of this study was to clarify the characteristics of falls in acute-care hospitals over time and by department. Methods: The subjects were hospitalized patients who fell between 2017 to 2021. We collected gender, sex, age, department, date of admission, date and time and place of fall, and purpose of action. The fall rate, injury rate, and number of days until the fall occurred were calculated. The time of occurrence was divided into three time periods: 6:00 to 14:00, 14:00 to 22:00, and 22:00 to 6:00. Results: Men always accounted for the majority of falls throughout the 5-year period, 52.7% of which were excretory-related and 59.6% of which occurred at the bedside. Falls occurred more frequently between 22:00 and 6:00 than at any other time, and the time from admission to fall was longer in the palliative care and orthopedic departments than in other departments. The rate of falls and injury were less variable, with the palliative care department consistently having the highest rate over the 5-year period. Conclusions: Gender, purpose of action, place of fall, and time of day supported previous studies, and it is considered necessary to continue to take measures paying attention to departments with high fall rates and the timing of falls in the future.